Corporate (Social) Responsibility under Authoritarianism: Interpretation, Communication, and Implementation in China - Kang, Xu (Taylor and Francis, 2025)
This book provides an in-depth exploration of corporate social responsibility (CSR) in the authoritarian context. It challenges prevailing CSR frameworks, which largely derive from liberal democratic contexts and overlook how political institutions shape the conceptualisation and practice of corporate responsibility. By situating CSR within China's political-economic system, the book sheds light on how CSR is dynamically interpreted, strategically communicated, and selectively implemented by corporate and state actors. Drawing on a mixed-method research design, the study analyses both qualitative and quantitative evidence. The analysis integrates policy documents, regulatory frameworks, CSR and sustainability reports from Chinese corporations, and in-depth qualitative interviews with corporate managers, NGO leaders, and experts. The findings highlight how CSR in China emerges through the normative interplay between market logics and power politics, involving various actors, including enterprises, state entities, and NGOs. The book also presents a critical account of how Chinese companies strategically adapt CSR discourses to align with governmental priorities while navigating complex stakeholder relationships. A book of vital interest to researchers in business ethics, international business and Asian studies, it will also appeal to practitioners and policymakers seeking to enhance strategies and policies for responsible business conduct.
CRIS-Team Scopus Importer:2025-12-19